Analisis Teknik Permainan Gitar Flamenco pada Lagu Fiebre Karya Benjamin Woods - Muhammad Farhan; Irdhan Epria Darma Putra (Universitas Palan, 2025)
This research aims to find out and describe the technique of playing flamenco guitar in the song Fiebre by Benjamin Woods. This type of research is descriptive qualitative research, with which this research will describe, describe and describe the flamenco guitar playing technique in the song Fiebre by Benjamin Woods. The object of research which is the center of attention and target of this research is the flamenco guitar playing technique in the song entitled fiebre by Benjamin Woods. The instrument in this research is the researcher himself, assisted by several tools to process the data. Get the sheet music for the song Fiebre with a flamenco guitar transcription adapted directly from the documentation of the performance of the song Fiebre by Benjamin Woods which was published on April 21 2020 on Benjamin Woods' official YouTube channel. The types of data used are primary data and secondary data. The steps for analyzing data are observation and documentation which are organized and interpreted as finding material to answer research problems. The results of the research show that the flamenco guitar playing techniques used in fiebre songs are picado, tirando, golpe, arpeggio, alzapua, and rasgueo. Benjamin Woods also uses a technique that was engineered by Benjamin Woods himself, namely the rasgueo abanico technique. This technique emerged because of Benjamin Woods' musical journey, which had a background in heavy metal music, which then made him want to present a sharper sound character with the rasgueo abanico technique.